A spider like map building robot to investigate the presence of objects in debris-cluttered - Ramachandran, Nagarajan, Prof. Dr.; Bukhari, Illias; Yew, Yum Wah; Yeoh, Shiau Yunn (Malaysian Association of Research Scientists (MARS), 2012)
The 10th Malaysian Technology Expo 2011 was organized by Malaysian Association of Research Scientists (MARS) and Professional Trade Exhibition and Meeting Planner (PROTEMP), 17th - 19th February 2011 at Kuala Lumpur Convention Centre (KLCC).